Revitalisasi Ekoteologi Lokal: Sebuah Upaya Mengatasi Krisis Lingkungan di Manggarai - Sandri, Yohanes Arnoldus; Cajambo, Yohanes Adi; Jani, Berno; Hardin, Maksimianus; Jindung, Pilipus Benizi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This research aims to (1) describe the environmental problems that hit the Manggarai community. (2) Describe the efforts to revitalise local Eco theology to overcome the environmental crisis in Manggarai. The research method used in this study is qualitative research. The results showed that environmental problems are one of the most serious problems faced by the Manggarai people and are even threatening their survival. Modern agricultural patterns, mining, illegal logging and lack of attention to local wisdom values are significant triggers for the clean water crisis, soil fertility degradation, and forest destruction. Efforts to revitalise local Eco theology are crucial in dealing with these problems. By viewing nature as a sacred entity, the mother of life, and a mediation to communicate with ancestral spirits and the Supreme Being, people will increasingly respect nature or reduce the act of exploitation of nature. The role of the church, government and society is crucial to internalise local wisdom education to the younger generation so that they do not behave destructively towards nature.